2021
DOI: 10.37506/ijfmt.v15i1.13791
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Changes with the age and their effect on plaque related disease

Abstract: Background: Saliva is an exocrine clear oral fluid predominantly secreted by salivary glands both major and minor. It consists of many constituents, mainly water and others are electrolytes, enzymes, immunoglobulins and other antimicrobial factors.Saliva plays an important role in the oral health, the level of its components change with age, and that has direct effect on teeth and periodontal tissue, because saliva plays a critical role in the development of dental caries and periodontal diseases.The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Moreover, [36] discovered that smoking has no effect on salivary IL-1 and IL-6 concentrations. [37] indicated that the concentration of α-amylase decreases with age, although the difference is not significant. However, the mean salivary α-amylase level did not differ substantially between males and females [38].…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, [36] discovered that smoking has no effect on salivary IL-1 and IL-6 concentrations. [37] indicated that the concentration of α-amylase decreases with age, although the difference is not significant. However, the mean salivary α-amylase level did not differ substantially between males and females [38].…”
Section: Resultsmentioning
confidence: 93%